Idiot's delight [videorecording (DVD)] - Brown, Clarence, 1890-1987; Gable, Clark, 1901-1960; Shearer, Norma, 1902-1983; Arnold, Edward, 1890-1956 (Turner Entertainment, 2010)
Gable stars as the head of a traveling group of singers when he meets a woman claiming to be a Russian aristocrat. He suspects she is someone he once knew in vaudeville, and sets out to prove it.